Mineralogical characterization of the clay fraction of vertisols from the Universidad Nacional de Piura parcel, San Lorenzo, Piura - Nima Ramírez, Fabian E. (2011)
In this paper we study the mineralogical characterization of the clay fraction of two samples of agricultural soils from Vertisols from the Valle de San Lorenzo, Piura Region, using analytical techniques such as energy dispersion X-ray fluorescence (XRF), X-ray difractometry (XRD) and transmission Mössbauer spectroscopy (TMS). Prior to their mineralogical characterization, the samples were subjected to physicochemical analysis such as measuring their pH, removal of organic matter and textural analysis. In this work we have used two samples, which have been referred to as M1 and M2 and drawn two different calicatas at a depth of 50 cm and 150 cm respectively. Mössbauer spectra were taken at room temperature. Analysis of both samples by XRF indicated that both samples have approximately the same concentration of Fe, which was approximately 3,5% and 3,9% for M1 and M2 respectively. It also notes the presence of some elements that serve as plant nutrients as Ca, K, Cu, Zn and Mn, which may be present in clay minerals as interlayer cations. The mineralogical analysis by XRD of both samples show the presence of phases of quartz, albite and clay minerals such as montmorillonite, illite (2:1 type) and kaolinite (1:1 type). The analysis by TMS of both samples showed the presence of Fe3+ paramagnetic cations occupying octahedral sites (cis and trans) in montmorillonite; additionally it is noted the presence of a paramagnetic doublet of Fe3+, which has been associated with tetrahedral sites in montmorillonite for having small isomeric shift and quadrupole splitting. Finally, a Fe2+ doublet has been observed which has not been associated with any specific mineral since its parameters superimpose with those for montmorillonite, illite and kaolinite. These results also indicate that iron is mainly distributed within the octahedral sites of montmorillonite in both samples.